Persepsi Guru Terhadap Proses Pengawasan oleh Kepala Sekolah di SMK Negeri Se-Kota Solok - Fitri Andriani; Nellitawati Nellitawati; Elizar Ramli (Jurnal Konseling dan Pendidikan, 2018)
The purpose of this research was look information on  the teacher perception about controlling of the headmaster on vocation senior high school. This is a descriptive research. The population is 201 teacher and research sample is 72 teachers who taken by simple random sampling. The instrument of this research was a questionnaire with Likert scale models that had tested for validity and reliability. Data analyzed using the average (mean) formula. The results of this research show teacher perception about controlling of headmaster on vocation senior high school (SMKN) in Solok city  stay in  good category with an average score 3,61 become 72,21 percent.